Российсkое общество сегодня в аспекте социализации молодёжи - Никандров, Николай Дмитриевич (International Dialogues on Education Journal, 2014)
In Russia, current practices in the education and socialization of the young are recognized as important parts of societal development. However, the success of such practices is made difficult through uncoordinated actions by socializing and educational institutions. Specific examples of such inconsistencies are analyzed along with the content of messages in respective materials pertaining to essential promises through media socialization and education. The necessity of programming of relevant societal processes is described, with consideration of differences in the interests of various groups and subjects. The article also discusses differences between Russia and the USA with regard to the socialization of the young.